Extraction, purification and characterization of pectinase from guava (Psidium guajava L.) peel - Ahmad Murshid, Fara Syazana (2022)
Pectinase brakes down pectin which is a polysaccharide that commonly found in plant cell wall. Mainly, enzymes are easily degraded with inappropriate method of extraction. Hence, it is important to employ an inexpensive, simple and efficient method of extraction. In this study, pectinase was extracted from guava (Psidium guajava) peel with ultrasound assisted extraction. The main effects namely sonication time, ultrasound temperature, pH of buffer and buffer to sample (B/S) ratio for optimization of the extraction were investigated. The optimum extraction condition was achieved at 20 min sonication time, 40 °C ultrasound temperature, at pH 5.0, using a 4:1 mL/g buffer to sample ratio. Conventional methods of purification are multistep, tedious and expensive. Therefore, the development of cost-effective, highly efficient and environmental friendly procedure for the purification of pectinase with desirable properties is considered essential. Subsequently, the potential application of aqueous two-phase system (ATPS) with Triton X-100 and sorbitol in the purification of pectinase from guava peel was demonstrated at laboratory scale. In this study, the effect of the main important parameters such as Tie Line Length (TLL), crude loads and pH on purification of the enzyme were investigated. The experimental results indicated that the pectinase was partitioned into surfactant-rich top phase, and the impurities were partitioned into the sorbitol-rich bottom phase with the novel method involving an ATPS composed of 25.0% (w/w) Triton X-100 and 26.0% (w/w) sorbitol at 50.2% of the TLL, 20% (w/w) of crude load and at pH 6.0. Based on the results, the calculated purification factor for the pectinase was 15.2 and the yield obtained was 98.3% for purified pectinase from guava peel. It was demonstrated that the phase components, Tie Line Length (TLL), crude loads and pH influenced the pectinase partitioning. This study proved that ATPS can be exploited as a successful, inexpensive and effective method for purification and recovery of the enzyme from a low-cost source with potential industrial application and alternative to the traditional ATPS. Characterization of the purified enzyme was performed to evaluate the stability of pectinase in different conditions. Characterization of the purified enzyme showed that pectinase extracted from guava peel was stable with the presence of some metal ions, inhibitors, surfactants and oxidizing agents. Metals ion such as K+, Ba+, Mg2+, Na+ and Mn2+ enhanced pectinase activity. Meanwhile, pectinase showed extreme stability with regards to surfactant and inhibitor including Triton X-100, Tween-80 and EDTA. The molecular weight of the pectinase was estimated to be 24.4 kDa based on SDS-PAGE. Therefore, it can be concluded that the enzyme with unique characteristics could be obtained from natural and cost-effective source and potentially contributed in the industrial applications including food and beverages, textile, paper, waste water treatment and other biotechnological applications.